Mycoplasma bovis subverts autophagy to promote intracellular replication in bovine mammary epithelial cells cultured in vitro - Yang Liu; Zhaoju Deng; Siyu Xu; Gang Liu; Yushan Lin; Sohrab Khan; Jian Gao; Weijie Qu; John P. Kastelic; Bo Han (Veterinary Research, 2021)
Abstract Mycoplasma species are the smallest prokaryotes capable of self-replication. To investigate Mycoplasma induced autophagy in mammalian cells, Mycoplasma bovis (M. bovis) and bovine mammary epithelial cells (bMEC) were used in an in vitro infection model. Initially, intracellular M. bovis was enclosed within a membrane-like structure in bMEC, as viewed with transmission electron microscopy. In infected bMEC, increased LC3II was verified by Western blotting, RT-PCR and laser confocal microscopy, confirming autophagy at 1, 3 and 6 h post-infection (hpi), with a peak at 6 hpi. However, the M. bovis-induced autophagy flux was subsequently blocked. P62 degradation in infected bMEC was inhibited at 3, 6, 12 and 24 hpi, based on Western blotting and RT-PCR. Beclin1 expression decreased at 12 and 24 hpi. Furthermore, autophagosome maturation was subverted by M. bovis. Autophagosome acidification was inhibited by M. bovis infection, based on detection of mCherry-GFP-LC3 labeled autophagosomes; the decreases in protein levels of Lamp-2a indicate that the lysosomes were impaired by infection. In contrast, activation of autophagy (with rapamycin or HBSS) overcame the M. bovis-induced blockade in phagosome maturation by increasing delivery of M. bovis to the lysosome, with a concurrent decrease in intracellular M. bovis replication. In conclusion, although M. bovis infection induced autophagy in bMEC, the autophagy flux was subsequently impaired by inhibiting autophagosome maturation. Therefore, we conclude that M. bovis subverted autophagy to promote its intracellular replication in bMEC. These findings are the impetus for future studies to further characterize interactions between M. bovis and mammalian host cells.